The Influence of GDP per Capita, Income Inequality, and Population on CO2 Emission (Environmental Kuznet Curve Analysis in Indonesia) - Rily Yunita; Toto Gunarto; Marselina Marselina; Dedy Yuliawan (Lafadz Jaya Publisher, 2023)
This study aims to prove the environmental kuznet curve (EKC) hypothesis in Indonesia and the effect of GDP per capita, income inequality, and population on CO2 emissions. This research uses a descriptive quantitative method. The data used is the time series from 1990-2021. The data analysis method used is the error correction model (ECM) to see the effect of the independent variables on the dependent variable in the short term and long term. The results of this study indicate that the EKC hypothesis is not proven in Indonesia either in the short term or in the long term. GDP per capita has a significant positive effect on CO2 emissions both in the short term and long term. Income inequality has no significant positive effect on CO2 emissions in the short term and no significant negative effect in the long term. The population has no significant negative effect on CO2 emissions in the short term and has a significant positive effect in the long term.